Expression of a G protein-coupled receptor (GPCR) leads to attenuation of signaling by other GPCRs: experimental evidence for a spontaneous GPCR constitutive inactive form - Tubio, María Rosario (2010)
The idea of G protein-coupled receptors (GPCRs) coupling to G protein solely in their active form was abolished when it was found that certain ligands induce a G protein-coupled but inactive receptor form. This receptor form interferes with signaling of other receptors by sequestering G protein. However, the spontaneous existence of this receptor species has never been established. The aim of the present work was to evaluate the existence of the spontaneous conformation of the receptor inactively coupled to G protein able to interfere with the response of other GPCRs. According to the law of mass action, receptor overexpression should lead to increased amounts of all spontaneously occurring species. Based on this, we generated Chinese hamster ovary (CHO-K1)-derived cell lines expressing various amounts of the human histamine H2 receptor. In these systems, the signaling of other endogenously and transiently expressed GPCRs was attenuated proportionally to human H2 receptor expression levels. G protein transfection specifically reverted this attenuation, strongly suggesting hijacking of the G protein from a common pool. Similar attenuation effects were observed when the β2- adrenergic receptor was overexpressed, suggesting that this is a more general phenomenon. Moreover, in human mammary MDA-MB-231 cells, a consistent increase in the response of other GPCRs was observed when endogenous expression of β2-adrenergic receptor was knocked down using specific small interfering RNAs. Our findings show that GPCRs may interact with the signaling of other receptors by modulating the availability of the G protein and suggest the existence of GPCR spontaneous coupling to G proteins in an inactive form.